STRUCTURE AT DEPTH AND SEDIMENTS OF THE SUBMARINE ALLUVIAL CONE OF THE DANUBE RIVER - Konyukhov A.I.; Ivanov M.K. (My University, 1989)
Analysis of seismoacoustic sections shows that the Danube suprafan is composed of deposits of a thick stratified sequence, in which members of relatively homogeneous (acoustically transparent) sediments alternate with horizons and series of beds with a complex layered-cellular structure. The sedimentary sequence in the middle of the suprafan, down to the lowest measured CSP interface, is about 750 m thick. It can be divided into four major units. The lowest has fairly homogeneous seismoacoustic properties and is bounded on top by a distinct subhorizontal surface. Several aggradation bodies of different age constitute the Danube submarine alluvial cone. As in other regions of the world, the study of thick sedimentary lenses of similar structure and origin is of both theoretical and practical interest. Oil and gas fields have already been proven in what are essentially submarine alluvial cones on extensions of the Mississippi and the Niger prodeltas, where the productive strata are the youngest so far known, i.e., Pleistocene.
Keywords: Pleistocene; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен